Arvidson, Teaching Nonmajors - Advice For Liberal Arts Professors - Nance, Star (Teaching History: A Journal of Methods, 2009)
Teaching non-majors can be a tedious task in the liberal arts college. Students might not engage academically and instead treat the course as "a waste of time." Differing attitudes fill the classroom and might cause interruptions, passive-aggressive behavior, or absenteeism. Teaching Nonmajors: Advice for Liberal Arts Professors addresses many roadblocks non-major students can create in the classroom. However, the text directs instructors to teach non-majors in a logical, positive, and student centered manner. Author P. Sven Arvidon does not start with the student, but the professor. He addresses essential guidelines professors incorporate into the syllabus, classroom environment, pedagogy, and professional development.